Deposition of resistant bacteria and resistome through FMT in germ‐free piglets. (11th May 2021) - Sun, J.; Chen, Y.L.; Ding, Y.C.; Zhong, H.; Wu, M.; Liu, Z.H.; Ge, L.P.
Abstract: Faecal microbiota transplantation (FMT) has received considerable attention in recent years due to its remarkable efficacy in restoring a normal gut microbiome. Here, we established the groups of post‐FMT recipient piglets using germ‐free piglets during early life to characterize the colonization of gut microbiota composition and the enrichment of resistance gene acquisition. By metagenomic analysis, we identified 115 bacterial phyla and 2111 bacterial genera that were acquired by the FMT recipients. We found that early‐life microbial colonization and the spread of resistomes in recipient piglets were age dependent. A total of 425, 425 and 358 AR genes primarily belonging to 114, 114 and 102 different types were detected in the donors, post‐FMT recipients in the FMT‐3D group and post‐FMT recipients in the FMT‐15D group respectively. Genes that encoded tetracycline, macrolide and chloramphenicol resistance proteins were the most dominant AR genes, and the results corresponded with the exposure of antibiotic consumption at farm. Bacteroides, Escherichia, Clostridium, Parabacteroides, Treponema, Lactobacillus and Enterococcus were significantly correlated with the distribution of AR genes. More importantly, the relative abundance of AR genes was positively correlated with the levels of mobile genetic elements. Our results indicate that early‐life microbial colonization can persistently shape the gut microbiota and antibiotic resistome. Abstract : Significance and Impact of the Study: Faecal microbiota transplantation (FMT) is expecting to be a potentially useful tool for promoting intestinal health and improving outcomes in farm animals. This study showed a critical period in which early‐life microbial exposure could have a profound influence on the enrichment of gut microbiota as well as transmission of antibiotic‐resistant genes between pigs through swine faeces, which corresponds to the pattern of antibiotic consumption in the pig farm. Therefore, in the future, it is necessary to deeply understand the sources of resistance gene acquisition and be more cautious with FMT in animals.